Factors influencing the efficiency of cellphone-based CBT for treating sleep disorders - Hu, Nannan; Xu, You; Mao, Hongjing (Frontiers in Psychiatry, 2022)
Objective: This survey aimed to better comprehend the factors influencing patient response to insomnia treatment. Methods: We conducted an online survey. A total of 1,395 patients completed the questionnaire at baseline. Insomnia, anxiety and depressive symptoms were evaluated using the Pittsburgh Sleep Quality Index (PSQI), 7-item Generalized Anxiety Disorder assessment (GAD-7) and 9-item Patient Health Questionnaire (PHQ-9), respectively. A total of 488 patients completed at least two surveys (baseline and monthly surveys thereafter) and reported that the online CBT was effective at the 1-year follow-up. The 488 patients were divided into three groups: the rapid (treatment effective at 4 weeks), intermediate (4-16 weeks), and delayed-response group (over 16 weeks). Results: Analysis of the demographic characteristics of the 488 patients did not reveal significant sex differences among the three groups(P=0.111). However, the groups significantly differed in age(P=0.001) and education (P=0.006). Compared to the rapid response group, the delayed-response group had a higher mean age (P <0.01) and a slightly lower level of education. The duration of the disorder was longer in the delayed-response group. Multivariate logistic regression showed that male sex, junior high school education, and higher PSQI were independent risk factors for the delayed response to treatment. Conclusion: Many factors affected the efficiency of insomnia treatment. Male sex, junior school education, and a high PSQI score predicted delayed response to insomnia treatment.